The Tools of Social Technologies in the Management System: Private and Public - ILYNYKH, Svetlana A.; MELNIKOV, Mikhail V.; SUCHORUKOVA, Natalia G.; ROVBEL, Svetlana V.; UDALTSOVA, Maria V. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
In the article, the authors consider the specifics of the term social technology and the use of social technology tools. The study is based on the fundamental ideas of sociology, comparative analysis, and interdisciplinary approach. The theoretical study is based on conceptual works and research results of Russian and foreign authors devoted to the analysis of the use of social technologies of management. It was determined, which tools are public and which-private. In the article, the authors present the results of an empirical study of the ideological and personnel tools of social technology in the management system. The assignment of social technology is the optimization of the managerial process for obtaining a socio-economic result. The management system, that functioning in the organization, is having the main share of the influence on the effectiveness of the company. Few managers are apt to revise the management principles. In the course of the study, a method of further training and career advancement has been demonstrated in the framework of personnel management, it has been established, that this method is not always effective. For social management, the problems of finding the most effective, existing tools that used in the areas of transformative or corrective social practice are still relevant. Management tools used within social technology of management are multiform. These include ideological, staffing, technological, socio-economic, and informational. It should be noted that the object of management – has a certain influence on what tools will be more effective. Rather, it is effective in different organizations on the different working conditions and gender affiliation. To improve management efficiency, it is necessary to use optimal tools in the technology of practical activity. Social experiments were conducted. Were selected organizations that are in the field of ‘Production’ (N = 40), ‘Trade’ (N = 45), ‘Construction’ (N = 50). To the tools of social technology in the management system belong ideological, staffing, technological, socio-economic, information. Ideological and personnel only were used. Tools can have public and private character. The results obtained in the study make it possible to supplement theoretical sociology in the aspect of sociology of management. The data obtained in the course of the experiment allowed establishing that the ideological management tool as a mission is not sufficiently used in organizations. Two principles are analyzed, the first is connected with personal connections, acquaintances, recommendations; the second principle was based on ads in the media, the Internet and public channels of communication. It has been established that age matters for men working in construction organizations. In organizations, management tools such as reassignment to higher positions, the ‘The board of honor’, are underused. The advanced training at the organization expense practically not used. At the respondents of the trade organization were not involved such personal motives as respect from the side of a Head, respect from the side of colleagues, and awareness of the social significance of their work. Most often, respondents point out such a way of training personnel as on-the-job training. This gives a certain positive result regardless of the organization. The research results can be used in further work on the problems of the tools of management.